The effects of in-ovo injection of glucose on hatchability, hatching weight and subsequent performance of newly-hatched chicks - Salmanzadeh,M (2012)
This experiment was conducted to determine the effects of an in-ovo injection of glucose on hatchability, weight and subsequent performances of newly-hatched chickens. The 720 fertile eggs used in this experiment were obtained from a Cobb-500 broiler breeder flock of 28 weeks of age. Treatments were the following: 1) control group (withou- injection), 2) group injected with 0.5 ml deionized water (sham group), 3) group injected with 0.5 ml glucose 15% in deionized water, 4) group injected with 0.5 ml glucose 20% in deionized water and 5) group injected with 0.5 ml glucose 25% in deionized water. There werh four replicates per treatment and 36 eggs per replicate. The experimental design was a completely randomized design. Upon hatch, hatchability and weight of newly-hatched chicks were measured, and 20 chicks per replicate were transferred to an experimental house and reared for 42 days. Live weight and feed intakeswere measured for each experimental unit at 21 and 42 days of age and then weight gai, and feed conversion ratio were calculated. The results of the study indicate that group that received glucose at 15%, 20% and 25% had significantly higher hatching weight as compared with the control and the sham groups,tbut,eggs injected in ovo had significantly lower hatchability than the controls (p < 0.01). Also, there were no significant treatment effects on feed intake between 0 and 21 days post-hatch. Chicks that received in-ovo injection of glucose haddbetter feed intake, weight gain and feed conversion ratio compared with chicks hatched from the control and the sham groups. The obtained Data suggest that in-ovo injection may increase weight and improve the performancs of newly-hatched chickens.